2017
DOI: 10.1159/000466708
|View full text |Cite
|
Sign up to set email alerts
|

Nonparallel Progression of Left Ventricular Structure and Function in Long-Term Peritoneal Dialysis Patients

Abstract: Background/Aims: Left ventricular hypertrophy and dysfunction are key cardiovascular risk factors of patients on peritoneal dialysis (PD). The purpose of this study was to investigate the dynamic changes of left ventricular (LV) structure and function in patients on long-term PD. Methods: Patients who underwent PD catheter insertions from January 2010 to December 2012 in our PD center were enrolled into this study. Cardiac structure and function of those patients were determined by echocardiography (4 times) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…Equally, the increased pressure, volume overload, anemia, hypocalcemia, and hyperphosphatemia usually result in compensatory myocardial hypertrophy and fibrosis, making diastolic dysfunction seem to be more common and occur earlier than systolic dysfunction in young uremic patients [14][15][16]. Furthermore, in our previous study, we found that patients with the normal LVEF, although under long-term regular peritoneal dialysis, maintaining well-controlled blood pressure and stable ultrafiltration and adequate total fluid removal, their LV diastolic function deteriorated as the CKD progressed, in contrast to the stable LV systolic function [17]. Therefore, it seems important to detect diastolic dysfunction at the early stage of peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 82%
“…Equally, the increased pressure, volume overload, anemia, hypocalcemia, and hyperphosphatemia usually result in compensatory myocardial hypertrophy and fibrosis, making diastolic dysfunction seem to be more common and occur earlier than systolic dysfunction in young uremic patients [14][15][16]. Furthermore, in our previous study, we found that patients with the normal LVEF, although under long-term regular peritoneal dialysis, maintaining well-controlled blood pressure and stable ultrafiltration and adequate total fluid removal, their LV diastolic function deteriorated as the CKD progressed, in contrast to the stable LV systolic function [17]. Therefore, it seems important to detect diastolic dysfunction at the early stage of peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 82%
“…When the condition continues to decompensate, the LAD, LVIDD, and LVIDS obviously enlarge, and LVEF will reduce. The increased cardiac preload will also result in the false appearance of increased LV output, which makes the LVEF of PD patients within the normal range [1,7]. Some studies have shown that mitral and aortic regurgitation can reduce the reliability of relevant indicators, and result in poor measurements, in which LVEF is preserved [8,9].…”
Section: Conventional Echocardiographymentioning
confidence: 99%
“…Related studies have shown that the number of uremic patients who die from cardiovascular events accounts for about 50% of the total deaths of dialysis patients [1]. Because of several traditional risk factors, including hypertension, diabetes, dyslipidemia, and smoking, and some nontraditional factors like protein carbamylation, oxidative stress, growth factors, and cytokines, cardiovascular diseases in young and middle-aged PD patients may develop earlier than in healthy agematched people [2], contributing to a higher incidence of cardiovascular diseases and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the advances in hemodialysis technology, the mortality and morbidity of ESRD patients on MHD remains high and the quality of life of these patients is poor [2]. Cardiovascular disease is a major complication of ESRD that is caused by metabolic and hemodynamic changes due to ESRD and is associated with high mortality [3,4], accounting for approximately 50% of hemodialysis patient deaths [5]. Left ventricular (LV) dysfunction is a critical indicator of cardiac dysfunction and an early clinical manifestation of LV hypertrophy.…”
Section: Introductionmentioning
confidence: 99%